(untitled) (The Pakistan Development Review, 2014)
Poverty analysis in developing countries including Pakistan has in general focused on poverty trends based on cross-sectional datasets, with very little attention being paid to dynamics—of transitory or chronic poverty. Transitory poor are those who move out or fall into poverty between two or more points of time whereas the chronic poor remain in the poverty trap for a significant period of their lives. The static measures of households’ standard of living do not necessarily provide a good insight into their likely stability over time. For instance, a high mobility into or out of poverty may suggest that a higher proportion of a population experiences poverty over time than what the cross-sectional data might show. 1 It also implies that a much smaller proportion of the population experiences chronic poverty contrary to the results of cross-sectional datasets in a particular year [Hossain and Bayes (2010)]. Thus, the analysis of poverty dynamics is important to uncover the true nature of wellbeing of population. Both the micro and macro level socio-demographic and economic factors are likely to affect poverty movements and intergenerational poverty transmission [Krishna (2011)].